Antiproliferative Activity of Hinokitiol, a Tropolone Derivative, Is Mediated via the Inductions of p-JNK and p-PLCγ1 Signaling in PDGF-BB-Stimulated Vascular Smooth Muscle Cells - Po-Sheng Yang; Meng-Jiy Wang; Thanasekaran Jayakumar; Duen-Suey Chou; Ching-Ya Ko; Ming-Jen Hsu; Cheng-Ying Hsieh (Molecules, 2015)
Abnormal proliferation of vascular smooth muscle cells (VSMCs) is important in the pathogenesis of vascular disorders such as atherosclerosis and restenosis. Hinokitiol, a tropolone derivative found in Chamacyparis taiwanensis, has been found to exhibit anticancer activity in a variety of cancers through inhibition of cell proliferation. In the present study, the possible anti-proliferative effect of hinokitiol was investigated on VSMCs. Our results showed that hinokitiol significantly attenuated the PDGF-BB-stimulated proliferation of VSMCs without cytotoxicity. Hinokitiol suppressed the expression of proliferating cell nuclear antigen (PCNA), a maker for cell cycle arrest, and caused G0/G1 phase arrest in cell cycle progression. To investigate the mechanism underlying the anti-proliferative effect of hinokitiol, we examined the effects of hinokitiol on phosphorylations of Akt, ERK1/2, p38 and JNK1/2. Phospholipase C (PLC)-γ1 phosphorylation, its phosphorylated substrates and p27kip1 expression was also analyzed. Pre-treatment of VSMCs with hinikitiol was found to significantly inhibit the PDGF-BB-induced phosphorylations of JNK1/2 and PLC-γ1, however no effects on Akt, ERK1/2, and p38. The up-regulation of p27kip1 was also observed in hinokitiol-treated VSMCs. Taken together, our results suggest that hinokitiol inhibits PDGF-BB-induced proliferation of VSMCs by inducing cell cycle arrest, suppressing JNK1/2 phosphorylation and PLC-γ1, and stimulating p27kip1 expression. These findings suggest that hinokitiol may be beneficial for the treatment of vascular-related disorders and diseases.